SUBJECT AND LANGUAGE INTEGRATED LEARNING TECHNOLOGY IN TEACHING A FOREIGN LANGUAGE - E., Omarov; Dosymbekova, Rauan; Sharypkazy, Nurtalip; Aizhan , Koibakova; Bakytnur, Maulit (International Journal of Psychosocial Rehabilitation, 2020)
The integrated subject-language approach to learning (hereinafter SLIL) is a broad concept that covers various situations of teaching a non-linguistic subject through a medium of a second or foreign language. SLIL assumes a balance between subject Subject and language learning. Thus, language is used as a means of studying the Subject, and in turn, is used as a resource for learning the language. Thus, in European countries there is an increased interest in the study and application of various methods of teaching a foreign language, the specificity of which is not the use of a foreign language as a learning objective, but its usage as a means of instruction.[1] In recent decades, important changes have taken place in the modern world, among which are: the creation of a worldwide Internet network and the globalization of all social, political, economic and environmental processes in the world. These, as well as other changes had a generally strong impact on the world education system.